Because I am compassionate: humanitarianism in the Book of the Covenant and cuneiform law - Nonnenmacher, David, Jr (Pickwick Publications, 2025)
"All of the law collections in the ancient world, both biblical and cuneiform, promoted humanitarian values--that is, justice for the lawbreaker and mercy for the needy. Scriptural passages advocating for the needs of the widow and the orphan, for example, find parallels within the prologues of their Near Eastern legal contemporaries. What is it, then, that makes the law of the Israelites stand out as "righteous" among the law collections of the surrounding nations as its author, Yhwh, claims (Deut 4:8)? With special attention to the Book of the Covenant (Exod 21-23), this study shows how biblical law possesses a unique, inherent, and innovative humanitarian outlook rooted in the compassionate character of Yhwh as modeled by his actions in the exodus narrative. God's proclamation of compassion in Exod 22:26 [27] serves as the initial focal point. Each subsequent chapter zooms out further in scope. Such compassion, this study asserts, not only establishes the basis for the Book of the Covenant's humanitarian values but also provides the motivation for its readers to live according to its directives."--Back cover